Exercise Heat Acclimation With Dehydration Does Not Affect Vascular and Cardiac Volumes or Systemic Hemodynamics During Endurance Exercise - Travers, Gavin; González-Alonso, José; Riding, Nathan; Nichols, David; Shaw, Anthony; Périard, Julien D. (Frontiers in Physiology, 2021)
Permissive dehydration during exercise heat acclimation (HA) may enhance hematological and cardiovascular adaptations and thus acute responses to prolonged exercise. However, the independent role of permissive dehydration on vascular and cardiac volumes, ventricular-arterial (VA) coupling and systemic hemodynamics has not been systematically investigated. Seven males completed two 10-day exercise HA interventions with controlled heart rate (HR) where euhydration was maintained or permissive dehydration (-2.9±0.5% body mass) occurred. Two experimental trials were conducted before and after each HA intervention where euhydration was maintained (-0.5±0.4%) or dehydration was induced (-3.6±0.6%) via prescribed fluid intakes. Rectal (Tre) and skin temperatures, HR, blood (BV) and left ventricular (LV) volumes, and systemic hemodynamics were measured at rest and during bouts of semi-recumbent cycling (55% V̇O2max) in 33°C at 20, 100 and 180 min. Throughout HA sweat rate (12±9 %) and power output (18±7 W) increased (P<0.05), whereas Tre was 38.4±0.2°C during the 75 min of HR controlled exercise (P=1.00). Neither HA intervention altered resting and euhydrated exercising Tre, BV, LV diastolic and systolic volumes, systemic hemodynamics, and VA coupling (P>0.05). Furthermore, the thermal and cardiovascular strain during exercise with acute dehydration post-HA was not influenced by HA hydration strategy. Instead, elevations in Tre and HR and reductions in BV and cardiac output matched pre-HA levels (P>0.05). These findings indicate that permissive dehydration during exercise HA with controlled HR and maintained thermal stimulus does not affect hematological or cardiovascular responses during acute endurance exercise under moderate heat stress with maintained euhydration or moderate dehydration.